2005
DOI: 10.1016/j.rmed.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of montelukast in stable patients with moderate to severe COPD

Abstract: This study aims to investigate the possibility of additional value of leukotriene receptor antagonist (LTA) on dyspnea score, arterial blood gases (ABG), pulmonary function tests (PFTs), and quality of life (St. George QoL) in chronic obstructive pulmonary disease (COPD) patients. In this randomized, prospective, single-blind, and controlled study, 117 non-reversible COPD patients defined by global initiative for chronic obstructive lung disease (GOLD) criteria were randomized to receive ipratropium bromide, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
3
39
0
1
Order By: Relevance
“…All of those have been implicated in the pathogenesis of airway hyperresponsiveness, damage and remodeling [18][19][20][21]. If operative in vivo, this mechanism may explain the therapeutic activity of CysLT 1 R antagonists, such as montelukast, in diseases such as COPD [22,23] and certain types of bronchial asthma, in which the neutrophil is thought to be the primary offender [24].…”
Section: Discussionmentioning
confidence: 99%
“…All of those have been implicated in the pathogenesis of airway hyperresponsiveness, damage and remodeling [18][19][20][21]. If operative in vivo, this mechanism may explain the therapeutic activity of CysLT 1 R antagonists, such as montelukast, in diseases such as COPD [22,23] and certain types of bronchial asthma, in which the neutrophil is thought to be the primary offender [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies of the clinical effects of LTRAs in COPD. For example, lung function improvement has been observed with zafirlukast in smokers with COPD (Cazzola et al, 2000;Nannini and Flores, 2003) Furthermore, a retrospective study of patients with moderate to severe COPD, reported that montelukast use improved patient's functional scores (shortness of breath, sputum production, wheezing, and nocturnal symptoms), use of drugs (oral and inhaled corticosteroids, inhaled bronchodilators, and supplemental oxygen), number of visits to the emergency department as well as the number and duration of hospitalizations for acute exacerbations (Rubinstein et al, 2004), and QL (Celik et al, 2005). However, further clinical studies are required to judge the real impact of LTRAs in COPD therapy or at least in a subset of patients with COPD (Usery et al, 2008).…”
Section: Cyslt In Other Diseasesmentioning
confidence: 99%
“…Adding theophylline, leukotriene antagonists or antihistamines in routine treatment protocol seem to ameliorate respiratory symptoms [21], improve PFT, dyspnea score and QOL in stable COPD [22], accordingly these agents were utilized wherever necessary. Oral tablets/capsules were preferred dosage form; however, it is highly recommended that physicians prescribe inhalers more than tablets/ capsules.…”
Section: Discussionmentioning
confidence: 99%